Pattern Electroretinogram Parameters Are Associated with Optic Nerve Morphology in Preperimetric Glaucoma after Adjusting for Disc Area - Tirsi, Andrew; Gliagias, Vasiliki; Moehringer, Julie; Orshan, Derek; Tello, Sofia; Derr, Peter; Park, Sung Chul; Obstbaum, Stephen A; Tello, Celso (Journal of ophthalmology, 2021)
Purpose. We examined the relationships between pattern electroretinogram and optical coherence tomography derived optic nerve head measurements, after controlling for disc area. Methods. Thirty-two eyes from 20 subjects with preperimetric glaucoma underwent pattern electroretinogram and optical coherence tomography. Pattern electroretinogram parameters (Magnitude, MagnitudeD, and MagnitudeD/Magnitude ratio) and optic nerve head measurements (rim area, average cup to disc ratio, vertical cup to disc ratio, cup volume, retinal nerve fiber layer thickness sectors, and Bruch’s membrane opening-minimum rim width thickness sectors) were analyzed after controlling for disc area. Results. Magnitude and MagnitudeD were significantly associated with rim area (r ≥ 0.503, p≤0.004). All pattern electroretinogram parameters significantly correlated with Bruch’s membrane opening-minimum rim width sectors—temporal superior and nasal inferior (r = 0.400, p=0.039)—and retinal nerve fiber layer sectors—superior, nasal superior, and inferior (r ≥ 0.428, p≤0.026). Magnitude and MagnitudeD explained an additional 26.8% and 25.2% of variance in rim area (B = 0.174 (95% CI: 0.065, 0.283), p=0.003, and B = 0.160 (95% CI: 0.056, 0.265), p=0.004), respectively. MagnitudeD and MagnitudeD/Magnitude ratio explained an additional 13.4% and 12.8% of the variance in Bruch’s membrane opening-minimum rim width global (B = 38.921 [95% CI: 3.872, 73.970], p=0.031, and B = 129.024 (95% CI: 9.589, 248.460), p=0.035), respectively. All Bruch’s membrane opening-minimum rim width sectors and retinal nerve fiber layer sectors (nasal superior, nasal inferior, and inferior) were significantly correlated with rim area (r ≥ 0.389, p≤0.045). Conclusion. PERG abnormalities can predict rim area loss in preperimetric glaucoma after controlling for disc area. We recommend controlling for disc area to increase diagnostic accuracy in early glaucoma.